Situs inversus totalis with solid pseudopapillary pancreatic tumor: A case report and review of literature. Issue 12 (March 2018) - Xiang, Deng; He, Jiannan; Fan, Zimeng; Xiong, Fangfang; Liu, Gang; Chen, Sufen; Wen, Wu; Li, Jianfeng; Ai, Junhua; Wan, Renhua; Wang, Gongxian; Shi, Jun
Abstract: Rationale: Situs inversus totalis (SIT) is a rare anatomical variation of the internal organs, and solid pseudopapillary tumor of the pancreas (SPTP) is a rare tissue type of pancreatic tumors, classified as benign or low-grade malignancy. However, to our knowledge, a patient with SIT and SPTP is extremely rare and has never been reported. Patient concerns: We retrospectively analyzed a case of SIT with SPTP in a 45-year-old woman. The main complaints were abdominal pain and sensation of heaviness for 2 weeks. There was tenderness and a mass that could be palpated in the right upper abdomen. Diagnoses: Heart ultrasonography (USG), chest x-ray, computed tomography (CT), and contrast-enhanced computerized tomography (CECT) revealed a mirror-image dextrocardia and inversion of all abdominal viscera and a space-occupying lesion in the pancreas tail. Abdominal computed tomography angiography (CTA) showed no obvious abnormality of artery. The diagnosis of SPTP was finally made by postoperative pathological examination. Interventions: The patient underwent resection of the pancreatic body and tail and splenectomy via laparotomy to completely remove the tumor. Outcomes: The patient was discharged with specific discomfort on postoperative day 7. At the 1.5-year follow-up, she recovered without issue. Lessons: Surgical resection remains the only effective treatment of SPTP. SIT with SPTP can be accurately diagnosed by heart USG, chest x-ray, CT, and CECT of the upper abdomen. Abdominal aorta CTA before surgery can decrease the injury risk of blood vessels.